Combined valve replacement and aortocoronary bypass in an adult mucopolysaccharidosis type VII patient - Marek, Josef; Kuchynka, Petr; Mikulenka, Vladimir; Palecek, Tomas; Sikora, Jakub; Hulkova, Helena; Lambert, Lukas; Linkova, Hana; Zemanek, David; Tesarova, Marketa; Linhart, Ales; Zeman, Jiri; et al. (Cardiovascular pathology, 2021)
Mucopolysaccharidosis type VII (MPS VII) is a rare autosomal recessive lysosomal storage disorder. MPS VII is caused by mutations in the GUSB gene that encodes β-glucuronidase. Adult MPS VII patients present with musculoskeletal abnormalities, coarse features, and corneal clouding. Cardiac and valvular impairment are common; however, severe valvular disease necessitating surgery has not yet been reported. We present a 32-year-old male MPS VII patient admitted to our hospital with decompensated heart failure. We identified aortic valve disease with severe stenosis (valve area 0.69 cm2) and moderate regurgitation. Severe mitral valve stenosis (valve area 1 cm2) with moderate to severe regurgitation was also found in the patient. In addition, an occlusion of the right coronary artery (RCA) was documented. The patient underwent surgical replacement of the mitral and aortic valves with mechanical prostheses and implantation of a venous bypass graft to his RCA. The surgery led to a significant improvement of his clinical symptoms. Six months after the procedure, both mechanical valves function normally. Histopathological assessment identified chronic inflammatory infiltrates, fibrosis and calcifications in both resected valves. Foamy cytoplasmic transformation was most evident in the valvular interstitial cells. The ultrastructural vacuolar abnormality seen in these cells corresponded to storage changes observed in other MPSs. In conclusion, we describe clinical findings and valvular pathology in an MPS VII patient with the first-reported successful combined surgical valve replacement and myocardial revascularization. The histological and ultrastructural analyses revealed that the lysosomal storage predominantly affected the valvular interstitial cells.
Keywords: aortální insuficience; aortální stenóza; Coronary Occlusion; mitrální insuficience; mitrální stenóza; Humans; Coronary Artery Bypass; Mitral Valve Stenosis; mukopolysacharidóza VII; Mucopolysaccharidosis VII; koronární okluze; mucopolysaccharidosis type VII; chirurgická náhrada chlopně; dospělí; coronary artery disease; výsledek terapie; lidé; Aortic Valve Stenosis; Sly syndrome; valvular disease; Mitral Valve Insufficiency; Adult; stupeň závažnosti nemoci; Male; koronární bypass; Treatment Outcome; Aortic Valve Insufficiency; cardiomyopathy; Severity of Illness Index; cardiac surgery; valve replacement; mužské pohlaví; Heart Valve Prosthesis Implantation